Will Hodgkinson's The House is Full of Yogis (2014) as an anti-conversion narrative. (2nd January 2019) - Ożarska, Magdalena
ABSTRACT: Representations of religious conversion are not very common in twenty-first-century Anglophone life writing, and those that exist are no longer limited to transitions between the world's major faiths. One of the few autobiographical texts featuring New Religious Movement conversions is Will Hodgkinson's The House is Full of Yogis. The Story of a Childhood Turned Upside Down (2014). Despite preserving the major components of a traditional conversion narrative, The House features some departures from the convention which ultimately turn it into an anti-conversion narrative. Among the most important is the fact that the results of the conversion as experienced by the convert's family seem far from satisfactory. It is only in his adulthood that the memoirist endorses his father's spiritual choices; as the memoir's adolescent 'narrated I', he is less keen to do so. Consequently, in contrast to the didactic purposes of conventional conversion narratives, The House fails to offer an unambiguous moral lesson. In generic terms, The House is a hybrid of a growing-up memoir and a Bildungsroman, which can be read as a reflection of British society's transition from the secular into its post-secular phase. This aspect of the novel seems to have escaped critical attention so far.